2016
DOI: 10.1038/srep22781
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on the quantity and quality of human cardiac stem cells

Abstract: Advanced age affects various tissue-specific stem cells and decreases their regenerative ability. We therefore examined whether aging affected the quantity and quality of cardiac stem cells using cells obtained from 26 patients of various ages (from 2 to 83 years old). We collected fresh right atria and cultured cardiosphere-derived cells (CDCs), which are a type of cardiac stem cell. Then we investigated growth rate, senescence, DNA damage, and the growth factor production of CDCs. All samples yielded a suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
3
14
2
Order By: Relevance
“…A recent study showed that human Isl1 pos c-kit pos CPC isolated from adult patients harbor an altered miRNA expression profile that correlated with a reduced proliferation capacity and abrogated response to growth factors compared to Isl1 pos c-kit pos CPC derived from neonates 22 . Another study, comparing CDCs derived from patients of various ages, showed limited differences in proliferation capacity, angiogenic potential and expression of growth factors between CDCs from young and elderly patients (≥65 years) 23 . However, in this study the youngest donor was 2 years old, the median age 72.5 years and 61.5% of them were 65 years or older which is in striking contrast with our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that human Isl1 pos c-kit pos CPC isolated from adult patients harbor an altered miRNA expression profile that correlated with a reduced proliferation capacity and abrogated response to growth factors compared to Isl1 pos c-kit pos CPC derived from neonates 22 . Another study, comparing CDCs derived from patients of various ages, showed limited differences in proliferation capacity, angiogenic potential and expression of growth factors between CDCs from young and elderly patients (≥65 years) 23 . However, in this study the youngest donor was 2 years old, the median age 72.5 years and 61.5% of them were 65 years or older which is in striking contrast with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although autologous stem cell transplantation holds some advantages, including safety of approach and reduction of virus or disease transmission; it also has disadvantages, namely the uncertainty of stem cell quality. Several studies have shown stem cell quality significantly decreases in older patients, and under certain conditions (Beane et al, 2014;Nakamura et al, 2016). Therefore, allogeneic stem cell therapy is regarded as a considered as suitable alternative to autologous transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Nakamura et al observed a good correlation with age in the expression of senescence markers in cardiosphere derived cells from aged hearts; but, no correlation was observed between age and growth rate, angiogenic ability and growth factor production. [ 8 ] These preliminary observations in human samples underscore the requirement for a systematic analysis of the variation in stem cell characteristics with age and disease, using an appropriate animal model. Deterioration in stem cell characteristics is possibly mediated by a suboptimal microenvironment.…”
Section: Introductionmentioning
confidence: 98%